Crédito Rural no contexto do desenvolvimento - Cardoso, João Luiz [UNESP] (Universidade Estadual Paulista (Unesp), 1983)
Análise das relações do crédito rural no processo de desenvolvimento agrícola e dos fatores que afetam a necessidade do crédito neste contexto.

The objectives of the present work are to anlyse contributions of rural credit in the process of agricultural development and factors which affect demand for rural credit in this process.
The role of rural credit in the process of development
Keywords: Crédito rural; Desenvolvimento; Capital; Poupança rural; Tecnologia; Rural credit; Development; Capital formation; Rural saving; Technology